Preparation, Characterization, In silico and In vitro Antimicrobial Studies of Phenothiazine-3-sulphonamide Derivatives - Eugene L Ayuk; Magdalene O Uchegbu; Peace I Ebiem-Kenechukwu; Timothy O Oni (Bioactivities, 2024)
The antibacterial activities of phenothiazine and sulphonamide derivatives have attracted so much interest. In this study, the synthesis and characterization of phenothiazine-3-sulphonamide derivatives and evaluation of their antimicrobial activity against the following pathogenic microorganisms is reported. Two Gram-positive bacteria; (Staphylococcus aureus (ATCC: 6538) and Streptococcus pyogenes (ATCC: 27853)), two Gram-negative bacteria; (Escherichia coli(ATCC: 3008), and Salmonella typhi (ATCC: 25175)) as well as one fungus (Aspergillus fumigatus (ATCC: 10231)) were used while ciprofloxacin, gentamycin and ketoconazole served as standard drugs. The synthesis of the derivatives was achieved through a base catalyzed the reaction of 4-chloroaniline with 1-naphthylamine to form 1-(naphthalen-1-yl)benzene-1,4-diamine. This intermediate was then treated with sulphur and iodine to yield the phenothiazine derivative while subsequent treatment of the phenothiazine compound with sulphonyl chlorides gave the final products. The synthesized compounds were characterized via proton nuclear magnetic resonance (1H-NMR), carbon-13 nuclear magnetic resonance (13C-NMR) and Fourier-transform infrared (FTIR) spectroscopic techniques. The minimum inhibitory concentration (MIC) of each compound was then determined using the agar well diffusion method. To predict the binding energies and patterns of the synthesized compounds with target proteins of the above-mentioned microorganisms, molecular docking simulations were run using Autodock Vina software (version 4.2). The spectra data of the compounds for FTIR, 1H-NMR and 13C-NMR spectral data were consistent with the assigned structures of the synthesized compounds. The binding energies (kcal/mol) for in silico antimicrobial studies were in the range -5.1 to -7.6 kcal/mol. The MIC values were in the range 3.5 to 1.0 mg/L. The results of the in vitro test revealed that the synthesized compounds exhibit promising antimicrobial activity and showed excellent bactericidal and fungicidal activities. The results obtained showed that the synthesized compounds possess drug-like properties and are good starting materials for drug production.